2001
DOI: 10.1016/s0142-694x(01)00002-3
|View full text |Cite
|
Sign up to set email alerts
|

Sketching as mental imagery processing

Abstract: Analysis of results of design protocols of novice and expert designers, although based on a limited number of designers, has shown that there are differences in the balance of cognitive actions between them. In this paper, we investigate the possible reasons for this imbalance in cognitive activity between the novice and expert designers in the rate of information processing driven by their relative experience in drawing production and sketch recognition. We use the theory of mental imagery to explain these di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
70
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(71 citation statements)
references
References 29 publications
1
70
0
Order By: Relevance
“…In this study three factors similar to those highlighted by Bilda et al (2006) and others (e.g., Kavakli and Gero, 2001;Neblett et al, in Finke, 1990) were explored in relation to how they might impact on flow: creative performance (self-perceived and objective measures), cognitive (working memory) load, and idea-execution congruence (disparity upon translation from internal to external perceptual feedback). All three were believed to have potential links to sense of task difficulty and trait MI vividness, which were also explored as possible influential variables in flow formation within visual creativity.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this study three factors similar to those highlighted by Bilda et al (2006) and others (e.g., Kavakli and Gero, 2001;Neblett et al, in Finke, 1990) were explored in relation to how they might impact on flow: creative performance (self-perceived and objective measures), cognitive (working memory) load, and idea-execution congruence (disparity upon translation from internal to external perceptual feedback). All three were believed to have potential links to sense of task difficulty and trait MI vividness, which were also explored as possible influential variables in flow formation within visual creativity.…”
Section: Discussionmentioning
confidence: 98%
“…When ideas are re-evaluated perceptually, the limitations of MI may become apparent and cause disruption. Discrepancies between internal predictions and external feedback (representational mismatch: Kavakli & Gero, 2001) may therefore also play a role in creative flow by introducing ambiguity and expectation violation which must be resolved before continuing. The role of perceptual feedback in flow might therefore depend on how well the implementation of an idea succeeds at the point of sensory verification, and the sense of congruence between idea simulations and their physical execution.…”
Section: Potential Confounding Effects Of Externalisation: Discrepancymentioning
confidence: 99%
“…This kind of information processing theory necessitates close attention to the information processing requirements of a task and thus is often useful in uncovering constraints on the learner that would not otherwise be apparent. We take sketching in conceptual design as a form of mental imagery processing (Kavakli and Gero, 2001). Mental imagery processing (Kosslyn et al, 1984) consists of image generation (drawing production), inspection (attention), transformation (reinterpretation), and information retrieval from a case base in long term memory.…”
Section: Strategic Knowledge Chunks and Cognitive Segmentsmentioning
confidence: 99%
“…In our previous studies, we found that the expert's cognitive activity and productivity (in terms of image generation) were three times as high as the novice's in the overall design process (Kavakli et al, 1999). We investigated the structure of cognitive actions in the design protocols, and found that there is evidence for the coexistence of the cognitive actions (Kavakli and Gero, 2001). Certain groups of cognitive actions increase and decrease in parallel with each other in the protocols of the novice and expert designers.…”
Section: Introductionmentioning
confidence: 99%
“…Sketches play multiple roles [1]: they serve as an external memory to augment the limitation of human cognitive abilities, act as the medium that users use to communicate, and serve as the triggers that enable reasoning [2]. Humans see in a sketch more than a static arrangement of arbitrary symbols: they always consider the meaning underlying the sketch and its potential transformations.…”
Section: Introductionmentioning
confidence: 99%